Immunotherapy for hepatocellular carcinoma in liver transplant patients (Literature review) - I. A. Dzhanyan; M. S. Novruzbekov; O. D. Olisov; D. I. Yudin; V. S. Rudakov; E. Yu. Antonova; I. V. Savchenko; I. V. Pogrebnyakov; V. V. Breder; M. Yu. Pitkevich (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Hepatocellular carcinoma (HCC) is the third cause of cancer-related mortality worldwide, accounting for more than 800,000 deaths annually. Surgical removal of the neoplasm remains the most effective treatment option. Partial liver resection is an adequate solution for patients without cirrhosis or with well-compensated cirrhosis, orthotopic liver transplantation is necessary in patients with early stage HCC on the background of cirrhosis. Tumor recurrence remains a major limitation of long-term survival of patients after liver transplantation. Posttransplant immunosuppression reduces the body's antitumor defense, which is provided by natural immunity. This contributes to the development and progression of the tumor process. Purpose of the study: to analyze domestic and foreign publications that present treatment options for HCC recurrence after liver transplantation. Literature sources were searched in PubMed, Scopus, Web of Science, MEDLINE, eLibrary databases. The search was conducted in Russian and English by keywords: hepatocellular carcinoma, tyrosine kinase inhibitors, immune checkpoint inhibitors, therapy of HCC relapse, orthotopic liver transplantation, RETREAT index, regorafenib, nivolumab. The authors presented a review of the data on the use of tyrosine kinase inhibitors and immune checkpoint inhibitors to prevent HCC recurrence. The results of the analysis of literature sources showed that the issue of post-transplant immunosuppression is relevant. The large number of studies and clinical case reviews leaves hope that an effective way of immunosuppression for recurrent HCC patients after liver transplantation will soon be found.